Avaliação do potencial antioxidante de beta-selenoaminas - Prestes, Alessandro de Souza (2013)
The antioxidant properties of selenium organic compounds have been largely investigated in the last decades, especially because the oxidative stress is directly related to various chronic-degenerative deseases. However, a few studies verify the action of nucleophlilic or electrophilic radicals on the protective activity of selenium compounds. In this work, it was evaluated the influence of different substituent radicals on the antioxidant activities of β-selenoamines. The capacity of β-selenoaminas in mimicry the glutathione peroxidase (GPx) activity and/or be substrate to the hepatic thioredoxinereductase (TrxR) enzyme were also investigated in experimental modelsin vitro.In DPPH assay, the β-selenoamines tested did not show antioxidant activity when compared to acorbic acid (AA). However, similar to compound (PhSe)2, the β-selenoamines with p-methoxy and tosylradicals were effective in preventing the lipid peroxidation induced by Fe2SO4. The compounds with other radicals did not exhibit the same activity. The β-selenoamine with the substituent group p-methoxy also showed mimetic activity to GPx and was reduced by hepatic TrxR. Furthermore, a positive correlation was observed among these parameters to β-selenoamines, which was not found in the results obtained with (PhSe)2. The data of this work show the influence of different substituent radicals on activity of organic selenium compounds and point the use of β-selenoaminas as pharmacological promissor compounds in in vivo experimental models.